Intermittent docetaxel chemotherapy in patients with castrate-resistant prostate cancer - Mountzios, I.; Bournakis, E.; Efstathiou, E.; Varkaris, A.; Wen, S.; Chrisofos, M.; Deliveliotis, C.; Alamanis, C.; Anastasiou, I.; Constantinides, C.; Karadimou, A.; Tsiatas, M.; et al. (Urology, 2011)
Objectives To determine whether intermittent docetaxel might control disease while limiting the toxicity and improving the quality-of-life parameters in patients with advanced, castrate-resistant prostate cancer. Intermittent docetaxel represents an appealing therapeutic approach. Methods We reviewed the records of 35 patients with chemotherapy-naive castrate-resistant prostate cancer who had received docetaxel 45 mg/m2 every 2 weeks, with oral prednisone 5 mg twice daily. Treatment was held when the patients had reached a >50% prostate-specific antigen reduction from baseline that was confirmed by a second measurement 4 weeks later, in the absence of disease progression. Docetaxel was resumed at a >25% prostate-specific antigen increase from the nadir level, also confirmed by a second measurement 4 weeks later, or in cases of documented disease progression. Results Of the 35 patients, 18 (51.42%) had entered the first chemotherapy-free interval (CFI) after a median of 6 infusions (range 2-12), 6 patients had entered a second CFI after a median of 4 months (range 2-12), and 1 patient, a third CFI at the last follow-up point. The median interval "off chemotherapy" was 4.5 months (range 1-16) for the first CFI. Two patients discontinued docetaxel because of Grade 4 nonhematologic toxicity. The median interval to treatment failure was 8.1 months (95% confidence interval 5.1-12.2) for the entire cohort and 12.2 months (95% confidence interval 8.3-25+) for the patients who had entered the first CFI. Conclusions The results of our study have shown that intermittent docetaxel is a clinically active and likely more tolerable and less costly therapeutic strategy for patients with castrate-resistant prostate cancer than continuous administration. Additional validation of this approach is warranted. © 2011 Elsevier Inc.